IMPLEMENTASI INTERNATIONAL PRIMARY CURRICULUM UNTUK MENUMBUHKAN KARAKTER TANGGUNG JAWAB SOSIAL - Hayuka Nawang Pawestri; Cindy Gupita Sari; Eny Winarti (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
In the implementation of the International Primary Curriculum, elementary schools provide collaborative spaces for students to contribute positively to others and the environment. This research aims to examine the implementation of the International Primary Curriculum at SD Cahaya Bangsa Utama Yogyakarta. A descriptive qualitative approach was employed in this study. Data were collected through observation, interviews, and documentation. The results show that: 1) teachers develop the social responsibility character based on the guidelines from the Unit of Work, which contains PjBL (Project Based Learning) activities, 2) teachers design activities to develop social responsibility character by incorporating three elements (psychological safety, empathy, and public speaking), 3) the tendency of students to dominate poses a challenge in efforts to cultivate social responsibility.